Syria from the Great War to civil war - McHugo, John 1951- (Saqi Books, 2014)
Syria's descent into civil war has already claimed an estimated 150,000 lives while nearly nine million people have fled their homes. This is now the greatest humanitarian and political crisis of the twenty-first century. In this hard-hitting book, John McHugo considers why Syria's foundations as a nation have proved so fragile. Tracing the history of Syria from the First World War to the present, McHugo lays bare the causes of the current tragedy. He takes in the country's thwarted attempts at independence, the legacies of the Anglo-French partition that fragmented it, and the failures of divisive French policies. He then turns to recent events: religious and sectarian tensions that have pulled Syria apart, the pressures of the Cold War and the Arab-Israeli dispute, and two generations of rule by the Assads. Did Syria ever have a chance? The conclusions drawn in this timely account are uncomfortable for both Westerners and Arabs alike.